THE STRUGGLE TO ACHIEVE A DREAM IN JAMES R. DOTY’S INTO THE MAGIC SHOP - Walanda, Keren; Rorintulus , Olga; Olii, Sanerita (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this research is to reveal the struggle of Jim to achieve his dream and the obstacles of his success. The writer uses qualitative methods, using two data sources, namely primary data and secondary data. The main data source is the novel of the main character, then the secondary data source is books, articles, and reference journals on the internet about the novel Into the Magic Shop by James R Doty. And in analyzing it the writer uses an objective approach that focuses on external and internal elements. The results show that the main character Jim's dream is to have a lot of money, go to college, become a successful doctor, and live a luxurious life. His struggles were when he studied magic, during his school life, and his business career. The obstacles he faces are finances, family, and the value of his courses. Finally, he can get what he dreams of, become a doctor and live what he wants.